Cut like wound - Nair, Anita (Haryana : HarperCollins, 2012)
"Introducing Inspector Borei Gowda... It is the first night of Ramadan. At Shivaji Nagar in the heart of Bangalore, a young male prostitute is killed and burnt alive. It would have stayed as yet another unsolved murder, but for Inspector Borei Gowda, the investigating officer. As bodies begin to pile up one after the other, and it becomes clear that a serial killer is on the prowl, Gowda recognizes a pattern in the killings which no one else does. Even as he negotiates serious mid-life blues, problems with his wife and son, an affair with an ex-girlfriend, and official apathy and ridicule, the killer moves in for the next victim... Steeped in the lanes and atmosphere of the city of Bangalore, Cut Like Wound introduces to the reader a host of unforgettable characters and is a brutal psychological thriller unlike any in Indian fiction."--
Keywords: India -- Bangalore; Murder -- Investigation; Transgender people